A pharmacoepidemiological study of prescription patterns of β2 sympathomimetic bronchodilators in exacerbation of non-severe asthma in tertiary care hospitals, not needing hospitalization - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Arformoterol, the (R, R) enantiomer of the racemic (R, R / S, S) diastereomer, formoterol, is a short and long acting β2 agonist bronchodilator. Levosalbutamol, the (R, R) enantiomer of racemic diastereomer (R, R / S, S) salbutamol, has a greater affinity for the β2 receptor. Occupation of β2 receptors by agonists result in the activation of the Gs-adenylyl cyclase-cAMP-PKA pathway, followed by phosphorylative events leading to bronchial smooth muscle relaxation. The aim of this pharmacoepidemiological study was to analyse the prescription patterns, and prescription content analysis, of arformoterol, levosalbutamol, formoterol or salbutamol, in non-severe asthma exacerbation in tertiary care hospitals, not needing hospitalization. Methods: It was a multi-centre, retrospective, observational and analytical study of 100 asthmatic patients’ hospital medical records, treated with 3 doses of arformoterol, levosalbutamol, formoterol or salbutamol nebulization, followed by peak expiratory flow rates (PEFR) measurement at the baseline and 6 minutes, after each dose; along with adverse effects recording. The number of prescriptions of 100 patients was recorded, the percentage of prescriptions was calculated, and the prescription content analysis was done. Results: PEFR of the patients showed significant increase after the first, second and third doses of bronchodilator nebulisation, with negligible adverse effects. Salbutamol was most commonly prescribed (45 prescriptions, 45%), followed by levosalbutamol (35 prescriptions, 35%), formoterol (15 prescriptions, 15%) and arformoterol (5 prescriptions, 5%). All aspects of prescription content analysis showed 100% completeness. Conclusions: Arformoterol was more effective, but equally safe, as compared to levosalbutamol, formoterol and salbutamol. Prescription frequency of salbutamol was followed by levosalbutamol, formoterol and arformoterol. Prescription content analyses showed 100% completeness.